MENINGKATKAN PARTISIPASI KAUM LAKI-LAKI MENGIKUTI PERAYAAN EKARISTI DALAM TERANG LIMA PERINTAH GEREJA DI PAROKI ST. YOSEP LITE KEUSKUPAN LARANTUKA - Rusae, Yohanes; Bulu Sinun, Maria Goreti (STIPAS Keuskupan Agung Kupang, 2022)
One of the Church's current concerns is the decreasing participation of men in participating in eucharistic celebrations. It cannot be denied that on Sundays, if we observe carefully, men go to church less than women. Men participate in the Euchrist celebration only during major holidays such as Christmas and Easter or when one of their family members wants to be baptized or wants to receive the sacrament of communion. The aim of this author is to find out why men participate less in eucharistic celebrations, to find out the inhibiting factors in celebrating the eucharist, and to know what efforts must be made to make men aware of the importance of the eucharist. The lack of men's participation in the eucharist celebration is caused by wrong thinking patterns, seeing the eucharist celebration in an unimportant way, there is no awareness within men to participate in the eucharist celebration. The reason why men are less likely to participate in eucharistic celebrations is because there are several factors: they are busy working such as cultivating the fields or gardening, playing cards at night, playing online games so they don't have time in the morning to go to church, and they are mentally lazy, you know.